STATE RELIGIOUS POLICIES AND THE EMERGENCE OF ATHEISM IN SAUDI ARABIA, 2000–2022 - Yuangga Kurnia Yahya; Umi Mahmudah (Arabic Literature Department, 2026)
In 2018, the International Humanist and Ethical Union (IHEU) reported that nine of the ten least atheist-friendly countries are Muslim-majority states, with the death penalty for apostasy and atheism cited as a key indicator. Despite such restrictions, surveys have suggested the presence of atheist identities in Saudi Arabia, although these figures are likely underestimated due to fear of persecution. This study examines the trajectories of conversion from Islam to atheism in a Muslim-majority country that applies Islamic law, focusing on Saudi Arabia during the period 2000–2022. Using a qualitative case study approach, the research relies on document analysis of state policies, international reports on religious freedom, and the writings of Abdullah al-Qasimi as a representative intellectual case. The findings indicate that restrictive religious governance, social control, and exposure to alternative ideas—particularly through digital media—contribute to the emergence of religious doubt and the formation of atheist identities among segments of Saudi society. The study also shows that strong religious socialization, combined with perceived injustice and limitations on freedom of belief, may intensify skepticism toward religious authority. These results suggest that discriminatory state policies may unintentionally foster intellectual resistance and curiosity toward atheistic ideas. By linking state policy, social conditions, and intellectual transformation, this study contributes to the sociology of religion by offering a new perspective on how structural constraints within highly conservative Islamic states shape trajectories toward atheism.